Research on the Status of Intangible Cultural Heritage Bearers in the Human Capital Perspective - Zhao, Jing; Wang, Zhong; Wang, Chenyu; Han, Liming; Ruan, Yaohui; Huangfu, Zhounan; Zhou, Shuai; Zhou, Lei (Frontiers in Psychology, 2022)
Culture is the bloodline of the nation and the spiritual home of the people. Intangible cultural heritage (ICH) belongs to the field of culture, and the transmission of ICH is a kind of human-based cultural transmission, which is the shaping of people's morality, character, sentiment, will, ideals and beliefs, value orientation, humanistic cultivation, artistic taste, way of thinking, wisdom, and ability in the practice of production and life of various ethnic groups. Based on the status acquisition model, this study analyzed the human capital (HC), social capital (SC), and psychological capital (PC) of ICH bearers from three perspectives. In addition to the conventional socio-demographic factors such as gender, age, place of residence, and education level as control variables, status attainment was introduced as a dependent variable, and occupational identity, job satisfaction, and entrepreneurial ability were introduced as mediating variables to construct a conceptual model in the hope of exploring the multiple influencing factors of status attainment among ICH bearers. Interviews were used to gain, the feelings and knowledge of experts, scholars, and ICH bearers, to lay a solid qualitative research foundation for this study. A questionnaire survey was also conducted to obtain basic information and professional experiences of ICH bearers to provide real support for the research analysis and discussion. As per the results of this research, all the hypotheses were supported except, HC did not have any significant impact on JS. Furthermore, SC was not in a significant association with career identity. Moreover, career identity and status attainment did not have a significant relationship.